The Knights of Labor and the Salvation Army: Religion and Working-Class Culture in Ontario, 1882-1890 - Marks, Lynne (Labour/Le Travailleur)

(untitled) (Canadian Committee on Labour History, 1991)
Abstract In the 1880S both the Knights of Labor, and the Salvation Army, which in this period was an exclusively revivalistic movement, drew mass support from Ontario's working class. This paper looks at the nature of working class support for the two movements, noting that the Salvation Army was more likly to attract working class women and unskilled men, while the Knights were most popular among skilled men. The possibility of overlap in membership is also addressed. In assessing the appeal of the two movements to working class Ontarians the relationship between working class religion and class consciousness is explored. Christianity was clearly important to many individual Knights, and fueled the Order's class conscious critique of nineteenth century society. The Salvation Army's otherworldly emphasis meant that it ignored contemporary social and economic issues; nonetheless the Army provided a distinctly working class religious alternative which was actively critical of the respectable mainstream churches. The popularity of both the Knights and the Army demonstrate the importance of class identity and religious belief within the late nineteenth century Ontario working class.